Pengaruh Gender dan Perbedaan Jurusan terhadap Kematangan Karir Mahasiswa Program Diploma Tiga Sekretaris Pendidikan Vokasi - Sovia Rosalin; Rini Agustina (JKI (Jurnal Konseling Indonesia), 2020)
This study aims to see the differences in career maturity of vocational students in terms of gender and type of majors. This research sample amounted 204 students (102 students majoring in Administration and office men and women, 102 students majoring in Library and Archives male and female) in the age range 18-20 years. The sampling technique used was random sampling. Data collection techniques using a career maturity scale compiled by the researcher. This study used a quantitative method with a 2x2 factor analysis tested with SPSS Corellation. The results showed that gender influenced student career maturity. The difference in majors also makes a significant contribution to the career maturity of students.